Intervenção em habilidades sociais com uma criança com síndrome de Down - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Santos, Larissa Helena Zani dos; Carlino, Fabiana Cristina (Universidade Federal de Santa Maria, 2014)
Studies show that children with Down’s syndrome have deficits in social skills, which can interfere in their social interactions and also in their academic performance. The aim of this study was to analyze the clinical significance and reliable change in repertory of social skills of a child with Down’s syndrome, from interventions in the clinic, at home and at school. A seven year old girl with Down’s Syndrome who had frequented the first year of regular school, her parents and her teacher participated in this study. They were attending in a Center of Applied Psychology, of a public university in São Paulo State. Before and after the intervention parents and teacher answered the Rating System Social Skills (SSRS). The intervention with the child had been conducted for six months, through playful activities in weekly meetings. It was discussed various topics related to social skills with parents and teacher in biweekly and monthly meetings. The results were analyzed using JT method. With parents, comparing the two assessments conducted, the data pointed to positive change reliable for four of the six skills assessed. Of the five skills assessed by the teacher, one of them was not in the clinical level since the first application. The other two went from clinical to non-clinical level, featuring reliable positive change. The study showed the importance of pre and post measures in case study, enabling the assessment of the effects of the intervention performed on the various factors of social skills. Further studies with larger populations may ratify the data obtained.

Estudos apontam que crianças com Síndrome de Down apresentam déficits em habilidades sociais, o que pode interferir nas suas interações sociais e, também, no seu desempenho acadêmico. O objetivo deste estudo foi analisar a significância clínica e mudanças confiáveis no repertório de habilidades sociais de uma criança com Síndrome de Down, a partir de intervenções na clínica, em casa e na escola. Participaram deste estudo uma menina de sete anos com Síndrome de Down, que freqüentava o primeiro ano do ensino regular, seus pais e sua professora. Eles eram atendidos em um Centro de Psicologia Aplicada, de uma universidade pública do interior paulista. Antes e depois da intervenção, pais e professora responderam ao Sistema de Avaliação de Habilidades Sociais (SSRS). A intervenção com a criança foi realizada durante seis meses, por meio de atividades lúdicas em reuniões semanais. Com os pais e professora, em encontros quinzenais e mensais, foram discutidos diversos temas relacionados às habilidades sociais. Os resultados obtidos foram analisados utilizando o método JT. Com os pais, comparando as duas avaliações conduzidas, os dados apontaram para mudança positiva confiável para quatro das seis habilidades avaliadas. Das cinco habilidades avaliadas pela professora, uma delas não estava no nível clínico desde a primeira aplicação. Das demais, duas passaram de nível clinico para não clínico, caracterizando uma mudança positiva confiável. O estudo mostrou a importância de avaliações pré e pós em estudo de caso, possibilitando a avaliação dos efeitos da intervenção realizada sobre os diversos fatores das habilidades sociais. Estudos futuros com populações maiores poderão referendar os dados obtidos.
Intervention in social skills with a child with Down’s syndrome
Keywords: Intervention; Social skills; Down’s syndrome; Intervenção com pais e professores; Habilidades Sociais; Síndrome de Down